Implementation of Bragança flour origin indication: Challenges and controversies in the process of regularization of houses of flour (Desenvolvimento em Questão, 2025)
Cassava flour is a food of indigenous origin found in all Brazilian states, with Pará being the main producer. Bragança flour stands out for being the most well-known and the only one with a Geographical Indication registration in the state. The research aims to analyze the regulation process of flour mills and how it impacts the development of the Bragança Flour IP territory. The research uses technical procedures, including bibliographic and documentary analyses, based on information provided by the Cooperativa Mista dos Agricultores Familiares e Extrativistas dos Caetés (Caetés Mixed Cooperative of Family Farmers and Extractivists) and government institutions. The Bragança Flour GI is still in its initial implementation phase, but challenges remain in this process, the biggest of which is the regularization of flour mills. The observation points out that there are a number of issues regarding the present and future of the Farinha de Bragança Indication of Origin that need to be reevaluated, involving the lack of public policies aimed at the flour production chain, revisions of documents, and informational, educational, and structural-organizational actions, as well as democratization of access to the GI sign, especially for small family producers.
Keywords: Geographical Indication; family production; standardization